Schizophrenia and physical illness: a coordinated care failure - Larsson, Lena G.; Olsson, Anna-Karin; Svensson, Ann; Johansson, Catrin (Frontiers in Psychiatry, 2025)
BackgroundPatients with schizophrenia have a significantly shorter life expectancy, emphasizing the need for better interventions for physical illness. Limited knowledge, unclear responsibilities, and insufficient collaboration between psychiatric and primary care services increase the risk of inadequate, uncoordinated, and delayed treatment for this vulnerable group. Therefore, the aim of this study was to explore healthcare professionals’ experiences regarding support, treatment, and interprofessional collaboration for patients with schizophrenia and physical illness.MethodA qualitative study with semi-structured interviews of nine psychiatric and primary care professionals. Data were analyzed using qualitative content analysis.ResultsThe analysis generated in an overall theme, Insufficient care coordination for patients with schizophrenia and physical illness of three categories, each with two subcategories. The first category, Inadequate internal clinical protocol, included the subcategories: difficulties in identifying physical illness and differing use of guidelines among healthcare institutions involved. The second category, Deficient division of responsibility included the subcategories: unclear defined division of responsibility for coordinating support and treatment and consequences of shared responsibility for pharmacotherapy. The third category, Lack of common clinical protocols included the subcategories: difficult to get in contact with one another and concrete suggestions concerning common clinical protocols.ConclusionTo counteract fragmented care for patient group, a more integrated care model is needed. The study highlights the importance of clearer allocation of responsibility, improved communication, standardized routines, and the implementation of coordinated individual care plans (CIP), as well as more user-friendly screening tools to enhance care quality and reduce the risk of treatment errors.